Characteristics of and variation in airborne ARGs among urban hospitals and adjacent urban and suburban communities: A metagenomic approach. (June 2020) - He, Peng; Wu, Yan; Huang, Wenzhong; Wu, Xinwei; Lv, Jiayun; Liu, Pengda; Bu, Li; Bai, Zhijun; Chen, Shouyi; Feng, Wenru; Yang, Zhicong
Graphical abstract: Highlights: A total of 643 ARGs subtypes belonging to 22 different ARG types were identified. The profiles of ARGs shown a city functional region dependent pattern. Airborne ARGs from the hospital exhibited higher ARG abundance and richness, may be the hotspots of resistant genes of multidrug and quinolone. Environmental ARGs from suburban community could be explained by human fecal pollution, and crAssphage could be applied to predict the abundance of ARGs. Abstract: Environmental antibiotic resistance genes (ARGs) have received much attention, while the characteristics of ARGs carried by particulate matter (PM) as a function of urban functional region are almost unknown. In this study, ARGs carried by PM2.5 and PM10 in an urban hospital, a nearby urban community and the nearest suburban community were detected using metagenomics. In total, 643 ARG subtypes belonging to 22 different ARG types were identified. The chloramphenicol exporter gene, sul1, bacA, and lnuA were the most abundant ARG subtypes in all air samples. The hospital exhibited higher ARG abundance and richness than the nearby communities. ARG profiles depended on functional region: hospital and suburban samples clustered separately, and samples from the nearby urban community interspersed among them. The representation of multidrug and quinolone resistance genes decayed with distance from the hospital to the urban community to the suburban community, indicating that hospital PM may be a hotspot for ARGs encoding proteins conferring multidrug and quinolone resistance. Airborne ARGs carried by PM in the hospital environment were more closely associated with clinically important pathogens than were those in nearby communities. In particular, carbapenemase genes, including blaNDM,   blaKPC,   blaIMP,   blaVIM,  and blaOXA-48, were discovered in hospital PM. In the suburban community, crAssphage, a human host-specific bacteriophage, was applied to predict ARG abundance and found to be enriched due to anthropogenic pollution but showed no clear evidence for ARG selection. In the hospital and the nearby urban community, the drivers of ARGs were complex. Our results highlighted that PM ARGs were closely related to human activities and revealed a potential hotspot, which could provide new evidence for further research and consequently mitigate the formation of airborne ARGs and transfer risks.